Joint power generation differentiates young and adult sprinters during the transition from block start into acceleration: A cross-sectional study - Debaere, S.; Vanwanseele, B.; Delecluse, C.; Aerenhouts, D.; Hagman, F.; Jonkers, I. (Sports Biomechanics, 2017)
The aim of this study was to investigate differences in joint power generation between well-trained adult athletes and young sprinters from block clearance to initial contact of second stance. Eleven under 16 (U16) and 18 under 18 (U18) promising sprinters executed an explosive start action. Fourteen well-trained adult sprinters completed the exact same protocol. All athletes were equipped with 74 spherical reflective markers, while an opto-electronic motion analysis system consisting of 12 infrared cameras (250Hz, MX3, Vicon, Oxford Metrics, UK) and 2 Kistler force plates (1,000Hz) was used to collect the three-dimensional marker trajectories and ground reaction forces (Nexus, Vicon). Three-dimensional kinematics, kinetics, and power were calculated (Opensim) and time normalised from the first action after gunshot until initial contact of second stance after block clearance. This study showed that adult athletes rely on higher knee power generation during the first stance to induce longer step length and therefore higher velocity. In younger athletes, power generation of hip was more dominant. ABSTRACT FROM AUTHOR